PENGARUH SERTIFIKASI TERHADAP PROFESIONALISME, KINERJA, DAN KESEJAHTERAAN GURU PADA MTsN DI SAMPIT KEMENTERIAN AGAMA KABUPATEN KOTAWARINGIN TIMUR - Nurhasanah, Nurhasanah (Jurnal Aplikasi Manajemen Pendidikan, 2015)
Teacher education is a subject that has a position to determine the success of education itself. With the teacher certification program is expected to increase professionalism, performance and welfare of teachers. This study was conducted in MTsN Sampit East Kotawaringin, with the title